Activation of the elderly – an individual level activity sheet and nursing home resident mobilization strategy - Goniewicz, Mariusz; Dzirba, Alina; Goniewicz, Krzysztof (Polish Journal of Public Health, 2013)
Being active enables compensation for disabilities, triggers repressed reinvigoration, modifies the one misdirected and stimulates activity, which is not awakened. Throughout the stay in the nursing home, the necessity of continuous implementation of various forms of reinvigoration is extremely important. Older people like any age group, need motivation to take on various forms of activity. Thus, improvement predictions as far as well-being, health and safety appear to be the most stimulating and motivating. However, sometimes you must choose detailed motifs according to individual nursing home resident.The paper presents the development methodology – an individual level activity sheet and nursing home resident mobilization strategy, which may be useful in the implementation of the nursing home plan activation.Every man’s dream is to be self-sufficient and independent. This applies particularly to elderly people. Due to the multitude problems of the elderly, it becomes necessary to take into account all deficits in their life, while planning any activities connected with care and rehabilitation. Nevertheless, no action can be isolated, detached from the context of the life activities. Additionally, they have to deal with current topics of everyday life of elderly, base on them, and stress the potential for further development of the nursing home resident at that age